Monitoring intramolecular proton transfer with ion mobility-mass spectrometry and in-source ion activation. Issue 12 (23rd January 2023) - Valadbeigi, Younes; Causon, Tim
Abstract : Here, we show how intramolecular proton transfer can be induced and monitored with the example of polycyclic aromatic amines using in-source ion-activation and ion mobility-mass spectrometry. Abstract : Here, we show how intramolecular proton transfer can be induced and monitored with the example of polycyclic aromatic amines using in-source ion-activation and ion mobility-mass spectrometry. Experiment and DFT calculations reveal that the protonation rate of C-atoms in aromatic rings is controlled by the energy barrier of intramolecular NH3 + → C proton transfer.